THE OPTIMIZATION OF MSCT OF URINARY TRACT USING TRACKING WITH FILTERS VARIATION - Nanang Sulaksono; Agustina Dwi Prastanti; Vederica Farida Candra (Jurnal Imejing Diagnostik (JImeD), 2019)
Backgroud: Kidney disease is a clinical situation which is indicated by the decreasing of kidney functions and MSCT is one of the modalities to diagnose that function. Aim to identify the differences in image information with filter variation abdomen medium smooth and  Mediastinum Standard.Methods: The method was the experimental research using research planning Post Test Only Group Design. The sampling was chosen consecutively. There were 3 Radiolog and  32 citra on the examination of MSCT abdomen without positive contrast media in Salatiga Public Hospital.Results :The intervention validity experiment after a tracking filter with variations, kruskal Wallis test results. There are meaningful differences shows vlue of p value 0,000 (p0,05), so that continued analysis of the Mann Whitney. The results of the analysis of the Mann Whitney pointed out that there is a difference between real or significant group of filter Medium Smooth Abdomen with Abdominal filter Medium Sharp/Mediastinum Standard Sig0.05 p value 0.000).Conclusion: a variation of the filter is able to identify the existence of a difference image information tracktus optimal unirarius MSCT abdomen after tracking by using the best filtr Medium Sharp Abdomen/Mediastinum Standard.